(3bQYI GdCfHjGA Ydjge GdUdGI hGdSdGes - (3eLghds
(3ChdgG (B:s
1- (3Sge BOe Ydjg GdSdGe bGd Gddg GdYXje jG BOe (B{(3GScf CfJ hRhLc GdLfI(B} (3hCfJ CjgG GdSGFd bO JZjQJ CMhGdcs
(3BNQgG (B:s
24- (3Sge eMeO (B-(3Udi Gddg Ydjg hSde(B- (3bGd Gddg GdYXje eMeO QShd Gddg GdBjI, hCfJ CjgG GdSGFd NQL dc Sge SjO GdNdb CLeYjfaGdc HMeO Gddg JYGdi hcf ef GdTGcQjf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf hGdMeO ddg QH GdYGdejfs
(3aj Chdg LOhd Hg CSeGA GdCfHjGA hCQbGeges
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJUha hGdBOGH GdTQYjIs